Theorizing American Studies : German Interventions into an Ongoing Debate - Sabine Sielke (European Journal of American Studies)
Partly due to the transdisciplinary agenda of the field, the development of American Studies has been accompanied by intensive debates about methods and theories. This essay relates a—necessarily reductive—narrative about how, throughout its history, German American Studies has intervened into and contributed to these debates; and how, with the emergence of parameters and politics of difference, on the one hand, and poststructuralist thought and notions of différance, on the other, the early debate on methods of American Studies transformed into discussions of theories of American literature, culture, history etc. In the light of what I perceive as the current division within German American Studies—a division between work that refocuses the theoretical discussion on literary studies and questions of aesthetics and analyses that engage other cultural practices and media by way of explicit theoretical perspectives, yet not necessarily in the frame of an American Studies agenda—my argument suggests that we take a more dialectical approach to the plurality of theories American Studies engages. While such an approach can no longer aim at syntheses and needs to allow for incoherencies and contradictions, it seems indispensable if we aim at futures for American Studies.1